A perovskite light-emitting diode based on ternary functional group synergistically enhanced interface passivation and a preparation method thereof
Through the ternary functional group collaborative enhancement interface passivation technology, the functional groups of 5-aminovaleric acid-trifluoroacetate passivation of FA and I vacancies are used to passivate the interface defect of perovskite light-emitting diodes, and the stability and Efficiency, achieving high external quantum efficiency and illuminance.
Patent Information
- Application Number
- CN202210623748.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-02
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2042-06-02
AI Technical Summary
Perovskite light-emitting diodes have a large number of defects at the interface between the surface and grains, resulting in non-radiative recombination, affecting their stability and efficiency. The existing interface passivation materials cannot effectively passivate multiple defects.
The ternary functional group synergistic enhancement interface passivation method is used, and 5-aminovaleric acid-trifluoroacetate is used as the passivator to passivate the FA and I vacancy defects through its functional groups such as -NH3+, -O- and -OH, respectively. The H-O…H-N bond is formed, which inhibits FA+ migration and thermal volatility, reduces the density of defect states, and improves carrier transmission.
It effectively reduces non-radiative recombination, improves the performance and stability of perovskite light-emitting diodes, has an external quantum efficiency of 22.3%, and an illuminance of 558.5Wsr-1m-2.
Smart Images

Figure CN114824119B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of perovskite light-emitting diodes, and specifically relates to a perovskite light-emitting diode based on ternary functional group synergistically enhanced interface passivation and a preparation method thereof. Background Art
[0002] Perovskite light-emitting diodes have been widely studied by scholars around the world due to their compatibility with flexible substrates, low manufacturing cost and high luminous efficiency. 3 Perovskite-based light-emitting diodes have achieved relatively high efficiency. However, the improvement of their stability is limited by the defect density in the perovskite material, especially the large number of vacancies and gaps on the surface of the perovskite and the interface between the grains, which leads to serious non-radiative recombination in the light-emitting diode. Interface passivation of perovskites is an effective means to reduce interface defects, but these passivation materials generally contain only one type of ion or molecule and cannot meet the passivation requirements of multiple interface defects. Summary of the invention
[0003] The purpose of the present invention is to provide a perovskite light-emitting diode based on ternary functional group synergistically enhanced interface passivation and a preparation method thereof.
[0004] The perovskite light-emitting diode based on ternary functional group synergistically enhanced interface passivation of the present invention is composed of an ITO conductive glass substrate, a zinc oxide nanoparticle (ZnO) electron transport layer, an ethoxy polyethyleneimine (PEIE) electron modification layer, a perovskite layer, a 5-aminovaleric acid-trifluoroacetate perovskite passivation layer, a poly (9,9-dioctylfluorene-CO-N-(4-butylphenyl) diphenylamine) (TFB) hole transport layer, a molybdenum trioxide (MoO 3 ) electrode modification layer and Au electrode.
[0005] The present invention uses 5-aminovaleric acid and trifluoroacetic acid as raw materials and synthesizes 5-aminovaleric acid-trifluoroacetate by a simple method. 5-aminovaleric acid-trifluoroacetate is dissolved in isopropanol to form a solution, which is spin-coated on the surface of perovskite. 3 + and trifluoroacetic acid-O - passivate FA vacancy defects and I vacancy defects respectively; in addition, the -OH of 5-aminovaleric acid can react with FA + Form HO…HN bonds, inhibit FA +Migration and thermal volatilization. The present invention uses 5-aminopentanoic acid-trifluoroacetate with three passivation functional groups to perform multi-passivation on perovskite. The three functional groups work together at the perovskite interface to reduce the defect state density, inhibit non-radiative recombination and improve carrier transport, thereby improving the performance and stability of the perovskite light-emitting diode; wherein the thickness of the perovskite layer is 30 to 50 nm, the thickness of the 5-aminopentanoic acid-trifluoroacetate perovskite passivation layer is 4 to 8 nm, the thickness of the ZnO electron transport layer is 10 to 30 nm, the thickness of the PEIE electron modification layer is 5 to 8 nm, the thickness of the TFB hole transport layer is 30 to 70 nm, and the thickness of the MoO 3 The thickness of the electrode modification layer is 5-7 nm, and the thickness of the Au electrode is 40-60 nm.
[0006] The preparation method of the perovskite light-emitting diode based on ternary functional group synergistically enhanced interface passivation described in the present invention comprises the following steps:
[0007] 1) Synthesis of 5-aminovaleric acid trifluoroacetate
[0008] 11-12 mg of 5-aminopentanoic acid is added to 5-6 mL of methanol to form a solution. Under an ice-water mixed bath, 12-13 mg of trifluoroacetic acid (excess) is slowly dripped into the methanol solution of 5-aminopentanoic acid, and stirring is continued for 1.5-2.5 h under the ice-water mixed bath condition; the obtained mixed solution is evaporated at 45-55° C. for 0.5-1.5 h until no obvious liquid remains and the obtained precipitate is recovered; the precipitate is dissolved in 1-1.2 mL of methanol and then recrystallized with ether; the step of "dissolving the precipitate with methanol and recrystallizing with ether" is repeated 3-5 times; the finally obtained solid is filtered and dried at 55-65° C. for 20-25 h under a nitrogen atmosphere to obtain 5-aminopentanoic acid-trifluoroacetate;
[0009] The structural formulas of 5-aminovaleric acid and 5-aminovaleric acid trifluoroacetate are shown in (a) and (b).
[0010]
[0011] 2) Substrate processing
[0012] The ITO conductive glass substrate was ultrasonically cleaned with detergent, acetone, isopropanol, and deionized water for 10 to 20 minutes, and then dried with nitrogen gas;
[0013] 3) Preparation of ZnO electron transport layer
[0014] Spin-coating ZnO nanoparticles (7-9 mg / mL, solvent: ethanol) on the surface of the cleaned ITO conductive glass substrate at a speed of 3500-4500 rpm for 25-35 seconds, thereby preparing a ZnO nanoparticle electron transport layer on the ITO conductive glass substrate with a thickness of 10-30 nm;
[0015] 4) Preparation of PEIE electronic modification layer
[0016] Dissolve 1.4-1.6 mg PEIE in 0.9-1.1 mL isopropanol to obtain a PEIE solution; spin-coat the PEIE solution on the ZnO nanoparticle electron transport layer at a speed of 4500-5500 rpm for 25-35 seconds, and then anneal at 95-105° C. for 8-12 minutes to obtain a PEIE electron modification layer with a thickness of 5-8 nm;
[0017] 5) Preparation of perovskite layer and its interface passivation layer
[0018] a) Preparation of perovskite precursor solution
[0019] 48-51 mg PbI 2 59-61 mg FAI and 5-6 mg ODEA are dissolved in 0.9-1.1 mL DMF, stirred at 500-700 rpm for 10-14 h at 55-65 °C to obtain a perovskite precursor solution;
[0020] b) Preparation of perovskite layer
[0021] Spin coating the perovskite precursor solution on the PEIE electronic modification layer at a speed of 2500-3500 rpm for 25-35 s, and annealing at 95-105° C. for 8-12 min to obtain a perovskite layer with a thickness of 30-50 nm;
[0022] c) Preparation of perovskite passivation layer
[0023] Add 1.5-2.5 mg of 5-aminopentanoic acid-trifluoroacetate to 9-11 mL of isopropanol to obtain a 5-aminopentanoic acid-trifluoroacetate solution. Spin-coat the 5-aminopentanoic acid-trifluoroacetate solution on the perovskite layer at a speed of 3500-4500 rpm for 25-35 s and anneal at 95-105°C for 2-5 min to obtain a 5-aminopentanoic acid-trifluoroacetate perovskite interface passivation layer with a thickness of 4-8 nm.
[0024] 6) Preparation of TFB hole transport layer
[0025] Under room temperature, 10-14 mg of TFB was dissolved in 0.9-1.1 mL of chlorobenzene to obtain a TFB solution; the TFB solution was spin-coated on the 5-aminopentanoic acid-trifluoroacetate perovskite interface passivation layer at a speed of 2500-3500 rpm for 25-35 seconds to obtain a TFB hole transport layer with a thickness of 60-80 nm;
[0026] 7) MoO 3 Preparation of electrode modification layer
[0027] At a pressure of 5×10 -4 ~8×10 -4 Under Pa conditions, 5-7 nm thick MoO was evaporated on the TFB hole transport layer. 3 , the growth rate is Get MoO 3 Electrode modification layer;
[0028] 8) Au electrode preparation
[0029] At a pressure of 5×10 -4 ~8×10 -4 Pa conditions, in MoO 3 The Au electrode with a thickness of 40 to 60 nm was deposited on the electrode modification layer at a growth rate of Then, the perovskite light-emitting diode based on the ternary functional group synergistically enhanced interface passivation layer of the present invention is prepared. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 : A schematic diagram of the structure of the perovskite light-emitting diode based on ternary functional group synergistically enhanced interface passivation according to the present invention;
[0031] Figure 2 : Schematic diagram of the effect of 5-aminovaleric acid-trifluoroacetate on the perovskite surface in the perovskite light-emitting diode based on ternary functional group synergistically enhanced interface passivation prepared by the present invention;
[0032] Figure 3 : EQE-current density curve and illumination-current density curve of the perovskite light-emitting diode based on ternary functional group synergistically enhanced interface passivation prepared by the present invention.
[0033] like Figure 1 As shown, 1 is an ITO conductive glass substrate, 2 is a ZnO electron transport layer, 3 is a PEIE electron modification layer, 4 is a perovskite layer covered by a TFB hole transport layer and a 5-aminovaleric acid-trifluoroacetate passivation layer, 5 is a MoO 3 Electrode modification layer, 6 is Au electrode.
[0034] like Figure 2As shown, a is a schematic diagram of the surface structure principle of the perovskite layer that has not been passivated by 5-aminopentanoic acid-trifluoroacetate, FA + and [PbI 6 ] 4- Represents FAPbI 3 The FA cation and [PbI 6 ] 4- Octahedral, with FA cation vacancies on the surface (V FA ), I anion vacancy (V I ) and other defects. b is a schematic diagram of the surface structure of the perovskite layer after passivation with 5-aminovaleric acid-trifluoroacetate. The -NH 3 + and trifluoroacetic acid-O - Passivate V FA and V I , the -OH of 5-aminovaleric acid and FA + Form HO…HN bonds, inhibit FA + Migration and thermal volatilization.
[0035] like Figure 3 As shown in the figure, the test results of the device performance using a quantum efficiency tester show that the external quantum efficiency (EQE) of the perovskite light-emitting diode passivated by 5-aminovaleric acid-trifluoroacetate reaches 22.3%, and the illumination reaches 558.5Wsr -1 m -2 , the horizontal axis is EQE, and the vertical axis is the current density (Current density) during the flow. DETAILED DESCRIPTION
[0036] Example 1
[0037] 1) Synthesis of 5-aminovaleric acid trifluoroacetate
[0038] 11.7 mg of 5-aminopentanoic acid was added to 5 mL of methanol to form a solution. 12.5 mg of trifluoroacetic acid (excess) was slowly dripped into the methanol solution of 5-aminopentanoic acid under ice-water mixed bath conditions, and stirring was continued for 2 h under ice-water mixed bath conditions; the obtained mixed solution was evaporated at 50°C for 1 h until no obvious liquid remained and the obtained precipitate was recovered; the precipitate was dissolved with 1 mL of methanol and then recrystallized with ether; the step of "dissolving the precipitate with methanol and recrystallizing with ether" was repeated 3 times; the finally obtained solid was filtered and dried at 60°C for 24 h under nitrogen atmosphere to obtain 5-aminopentanoic acid-trifluoroacetate; the product was analyzed by Fourier infrared absorption test, and the characteristic peaks of trifluoroacetic acid and 5-aminopentanoic acid materials were compared to obtain 5-aminopentanoic acid-trifluoroacetate product.
[0039] 2) Substrate processing
[0040] The ITO conductive glass substrate was ultrasonically cleaned with detergent, acetone, isopropanol, and deionized water for 15 minutes, and then dried with nitrogen gas;
[0041] 3) Preparation of ZnO electron transport layer
[0042] ZnO nanoparticles (8 mg / mL, solvent: ethanol) were spin-coated on the surface of the cleaned ITO conductive glass substrate at a speed of 4000 rpm for 30 seconds, thereby preparing a ZnO nanoparticle electron transport layer on the ITO conductive glass substrate with a thickness of 20 nm.
[0043] 4) Preparation of PEIE electronic modification layer
[0044] 1.5 mg PEIE was dissolved in 1 mL isopropanol to obtain a PEIE solution; the PEIE solution was spin-coated on the ZnO nanoparticle electron transport layer at a speed of 5000 rpm for 30 seconds, and then annealed at 100°C for 10 minutes to obtain a PEIE electron modification layer with a thickness of 6 nm;
[0045] 5) Preparation of perovskite layer and its interface passivation layer
[0046] a) Preparation of perovskite precursor solution
[0047] 49 mg PbI 2 , 60 mg FAI and 5.8 mg ODEA were dissolved in 1 mL DMF, and stirred at 600 rpm for 12 h at 60 °C to obtain a perovskite precursor solution;
[0048] b) Preparation of perovskite layer
[0049] The perovskite precursor solution was spin-coated on the PEIE electronic modification layer at a speed of 3000 rpm for 30 s and annealed at 100 °C for 10 min to obtain a perovskite layer with a thickness of 40 nm.
[0050] c) Preparation of perovskite passivation layer
[0051] 2 mg of 5-aminopentanoic acid-trifluoroacetate was added to 10 mL of isopropanol to obtain a 5-aminopentanoic acid-trifluoroacetate solution. The 5-aminopentanoic acid-trifluoroacetate solution was spin-coated on the perovskite layer at a speed of 4000 rpm for 30 seconds and annealed at 100°C for 3 minutes to obtain a 5-aminopentanoic acid-trifluoroacetate perovskite interface passivation layer with a thickness of 5 nm.
[0052] 6) Preparation of TFB hole transport layer
[0053] 12 mg of TFB material was dissolved in 1 mL of chlorobenzene to obtain a TFB solution; the TFB solution was spin-coated on the 5-aminovaleric acid-trifluoroacetate perovskite interface passivation layer at a speed of 3000 rpm for 30 seconds to obtain a TFB hole transport layer with a thickness of 70 nm;
[0054] 7) MoO 3 Preparation of electrode modification layer
[0055] At a pressure of 7×10 -4 Under Pa conditions, 6 nm thick MoO was evaporated on the TFB hole transport layer. 3 , the growth rate is
[0056] 8) Au electrode preparation
[0057] At a pressure of 7×10 -4 Pa conditions, in MoO 3 The Au electrode is deposited on the layer with a thickness of 50nm and a growth rate of Then, the perovskite light-emitting diode based on the ternary functional group synergistically enhanced interface passivation layer of the present invention is prepared.
Claims
1. A method for preparing a perovskite light-emitting diode based on ternary functional group synergistically enhanced interface passivation, the steps of which are as follows: 1) Substrate processing The ITO conductive glass substrate was ultrasonically cleaned with detergent, acetone, isopropanol, and deionized water for 10 to 20 minutes, and then dried with nitrogen gas; 2) Preparation of ZnO electron transport layer Spin-coating ZnO nanoparticles (7-9 mg / mL, solvent: ethanol) on the surface of the cleaned ITO conductive glass substrate at a speed of 3500-4500 rpm for 25-35 seconds, thereby preparing a ZnO nanoparticle electron transport layer on the ITO conductive glass substrate with a thickness of 10-30 nm; 3) Preparation of PEIE electronic modification layer Dissolve 1.4-1.6 mg PEIE in 0.9-1.1 mL isopropanol to obtain a PEIE solution; spin-coat the PEIE solution on the ZnO nanoparticle electron transport layer at a speed of 4500-5500 rpm for 25-35 seconds, and then anneal at 95-105° C. for 8-12 minutes to obtain a PEIE electron modification layer with a thickness of 5-8 nm; 4) Preparation of perovskite layer and its interface passivation layer a) Preparation of perovskite layer Spin coating the perovskite precursor solution on the PEIE electronic modification layer at a speed of 2500-3500 rpm for 25-35 s, and annealing at 95-105° C. for 8-12 min to obtain a perovskite layer with a thickness of 30-50 nm; b) Preparation of perovskite passivation layer 1.5-2.5 mg of 5-aminopentanoic acid-trifluoroacetate is added to 9-11 mL of isopropanol to obtain a 5-aminopentanoic acid-trifluoroacetate solution, and the 5-aminopentanoic acid-trifluoroacetate solution is spin-coated on the perovskite layer at a speed of 3500-4500 rpm for 25-35 s, and annealed at 95-105° C. for 2-5 min to obtain a 5-aminopentanoic acid-trifluoroacetate perovskite interface passivation layer with a thickness of 4-8 nm; 5) Preparation of TFB hole transport layer Under room temperature, 10-14 mg of TFB was dissolved in 0.9-1.1 mL of chlorobenzene to obtain a TFB solution; the TFB solution was spin-coated on the 5-aminopentanoic acid-trifluoroacetate perovskite interface passivation layer at a speed of 2500-3500 rpm for 25-35 seconds to obtain a TFB hole transport layer with a thickness of 60-80 nm; 6) Preparation of MoO3 electrode modification layer At a pressure of 5×10 -4 ~8×10 -4 Pa conditions, 5-7 nm thick MoO3 was evaporated on the TFB hole transport layer at a growth rate of Obtaining a MoO3 electrode modification layer; 7) Au electrode preparation At a pressure of 5×10 -4 ~8×10 -4 Pa conditions, a 40-60 nm thick Au electrode was deposited on the MoO3 electrode modification layer at a growth rate of Then, the perovskite light-emitting diode based on the ternary functional group synergistically enhanced interface passivation layer of the present invention is prepared.
2. The method for preparing a perovskite light-emitting diode based on ternary functional group synergistically enhanced interface passivation according to claim 1, characterized in that: 11-12 mg of 5-aminopentanoic acid is added to 5-6 mL of methanol to form a solution. In an ice-water mixed bath, 12-13 mg of trifluoroacetic acid (excess) is slowly dripped into the methanol solution of 5-aminopentanoic acid, and stirring is continued for 1.5-2.5 h under the ice-water mixed bath condition. The obtained mixed solution is evaporated at 45-55° C. for 0.5-1.5 h until no obvious liquid remains and the obtained precipitate is recovered. The precipitate is dissolved in 1-1.2 mL of methanol and then recrystallized from ether. The steps of "dissolving the precipitate in methanol and recrystallizing from ether" are repeated 3-5 times. The finally obtained solid is filtered and dried at 55-65° C. for 20-25 h under a nitrogen atmosphere to obtain 5-aminopentanoic acid-trifluoroacetate. The structural formulas of 5-aminopentanoic acid and 5-aminopentanoic acid-trifluoroacetate are shown in (a) and (b).
3. The method for preparing a perovskite light-emitting diode based on ternary functional group synergistically enhanced interface passivation according to claim 1, characterized in that: 48-51 mg PbI2, 59-61 mg FAI and 5-6 mg ODEA were dissolved in 0.9-1.1 mL DMF, and stirred at 500-700 rpm for 10-14 h at 55-65° C. to obtain a perovskite precursor solution.
4. The method for preparing a perovskite light-emitting diode based on ternary functional group synergistically enhanced interface passivation according to claim 1, characterized in that: 5-Aminopentanoic acid-trifluoroacetate with three passivating functional groups was used to perform multi-passivation on perovskite.
5. A perovskite light-emitting diode based on ternary functional group synergistically enhanced interface passivation, characterized in that: The method is prepared by any one of claims 1 to 4.
Citation Information
Patent Citations
Perovskite quantum dot light emitting diode containing two-dimensional perovskite passivation layer and preparation method thereof
CN110350105A
Green perovskite light-emitting diode based on surface post-treatment process and preparation
CN111785846A